The Application Of The Stad Type Cooperative Model To Increase Student Learning Motivation In Learning Pancasila Education In Class Vi A SDN 42 Kota Bengkulu - Destri Lencana; Ronalia, Viona Bunga; Teri Anita; Harri Silaban; Nabila, Hazizah Putri; Neza Agusdianita; Yusnia, Yusnia (Jurnal Multidisiplin, 2024)
This study aims to analyze the application of STAD type cooperative model to increase students' learning motivation in Pancasila Education learning in class VI A SD N 42 Bengkulu City. Lesson Study is a collaborative approach that allows teachers to plan, observe and reflect on learning in groups, with the aim of improving teaching quality and student learning outcomes. In this study, various aspects such as planning, implementation, and reflection were observed to identify the constraints and impact of Lesson Study on students' learning motivation. Data were collected through observation, questionnaires, and interviews. This research is expected to provide theoretical and practical benefits for improving the quality of education, both for students, teachers, and schools.